Decision making and heart rate variability: A systematic review. Issue 1 (19th January 2022) - Forte, Giuseppe; Morelli, Matteo; Grässler, Bernhard; Casagrande, Maria
Abstract: Heart rate variability (HRV) reflects the balance of the autonomic nervous system and is associated with cognitive functions. However, its relationship with the process related to making a decision is unclear. This systematic review aims to analyze the relationship between HRV and decision‐making. A qualitative analysis was conducted according to the PRISMA‐Statement. Fifteen studies were included, with a total of 1051 healthy participants. Our results show an association between higher vagally mediated HRV and better decision‐making performance, especially under risk and uncertainty. At the same time, a lower HRV is associated with lower performance in developing good decisions. This systematic review highlights the influence of the autonomic nervous system in decision‐making processes. HRV could be considered a biomarker of making decisions. However, the nature of this relationship is still difficult to clarify, and further studies are needed.